2017
DOI: 10.1039/c7ce01053b
|View full text |Cite
|
Sign up to set email alerts
|

A cerium-based metal–organic framework having inherent oxidase-like activity applicable for colorimetric sensing of biothiols and aerobic oxidation of thiols

Abstract: A cerium-based MOF exhibits oxidase-like activity for colorimetric sensing of biothiols and aerobic oxidation of thiols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 71 publications
1
56
0
1
Order By: Relevance
“…The studies by Cao et al (2017) revealed that ruthenium nanoparticles (Ru) exhibit their own oxidase activity, catalyzing the oxidation of tetramethylbenzidine (TMB) and sodium L-ascorbate with dissolved oxygen. Similar activity was demonstrated by Pt nanoparticles (Deng et al, 2017), Au (He et al, 2011), Ir (Cui et al, 2017), CoFe 2 O 4 (Zhang et al, 2013), ZnFe 2 O 4 (Su et al, 2012), MnO 2 (Yan et al, 2017), CeO 2 (Dalapati, 2017;Estevez et al, 2017), NiCo 2 O 4 (Song et al, 2018), Se (Guo et al, 2016) and other metals and composites. It was determined that the maximum mimetic activity depends on particular physical parameters.…”
Section: Nanomaterials As Oxidase Mimeticssupporting
confidence: 61%
“…The studies by Cao et al (2017) revealed that ruthenium nanoparticles (Ru) exhibit their own oxidase activity, catalyzing the oxidation of tetramethylbenzidine (TMB) and sodium L-ascorbate with dissolved oxygen. Similar activity was demonstrated by Pt nanoparticles (Deng et al, 2017), Au (He et al, 2011), Ir (Cui et al, 2017), CoFe 2 O 4 (Zhang et al, 2013), ZnFe 2 O 4 (Su et al, 2012), MnO 2 (Yan et al, 2017), CeO 2 (Dalapati, 2017;Estevez et al, 2017), NiCo 2 O 4 (Song et al, 2018), Se (Guo et al, 2016) and other metals and composites. It was determined that the maximum mimetic activity depends on particular physical parameters.…”
Section: Nanomaterials As Oxidase Mimeticssupporting
confidence: 61%
“…Comparison of the kinetic constants of FeN5 SA/CNF and nanozymes. References (44)(45)(46)(47)(48)(49)(50)(51)…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Other examples in the literature reporting the use of UiO-66 type materials as catalysts for the oxidation of benzyl alcohol, [42] thiophenol, [43] cyclohexene [44] and Ti IV supported as part of the node in UiO-66 for the oxidation of cyclohexene using hydrogen peroxide [45] have also been reported.…”
Section: Nodes As Redox Sitesmentioning
confidence: 99%